Secure Distributed Cloud Storage based on the Blockchain Technology and Smart Contracts - Solonas Gousteris; Yoannis C. Stamatiou; Constantinos Halkiopoulos; Hera Antonopoulou; Nikos Kostopoulos (Ital Publication, 2023)
Objectives: This paper addresses the problem of secure data storage and sharing over cloud storage infrastructures. A secure, distributed cloud storage structure incorporating the blockchain structure is proposed that supports confidentiality, integrity, and availability. Methods/Analysis: The proposed structure combines two well-known technologies: one of them is the Ethereum Blockchain and its Smart Contracts and the other is the RSA encryption and authentication scheme. The Ethereum Blockchain is used as a data structure, which ensures data availability and integrity while RSA provides sensitive data confidentiality and source authentication. Findings: As a result, users of the proposed structure can trust it and be certain that they can securely exchange information through a publicly accessible and shared cloud storage. The application can be used either through a user interface (UI) or a command-line interface (CLI). Novelty /Improvement:The novelty of this work is that the system that is proposed could be used for secure data storage on the cloud as well as for file sharing and authentication verification. Also, secure data storage and file sharing are already offered by the proposed system. Doi: 10.28991/ESJ-2023-07-02-012 Full Text: PDF